The social needs and problems of higher education students with impairments - Crous, Faan (University of the Free State, 2004)
There has been a huge influx of students with impairments into higher education, mainly as a result of legislation in this regard. In the light of this development, research was undertaken to determine the social needs and problems experienced by a group of higher education students with impairments in South Africa. A survey of 751 students at three universities showed that students with impairments comprised less than 0.5% of the student population. It appears from this survey that the general perception of students with impairments is that people without impairments have little or no understanding of them and/or their circumstances. The majority of students with impairments felt that they were not easily accepted by other students and that they themselves did not find it easy to make friends with other students.

Gedurende die afgelope aantal jare is daar ’n groot toename in die aantal hoër onderwysstudente met gestremdhede. Hierdie toename kan grootliks toegeskryf word aan wetgewing in hierdie verband. In die lig van hierdie ontwikkelinge is navorsing gedoen om te bepaal wat die sosiale behoeftes en probleme van studente met gestremdhede in die hoëronderwys is. Uit ’n ondersoek by drie Suid-Afrikaanse universiteite waarby 751 studente betrokke was, is gevind dat studente met gestremdhede minder as 0.5% van die totale studentegemeenskap uitmaak. Volgens die bevindinge van hierdie ondersoek blyk dit dat studente met gestremdhede van mening is dat niegestremdes min of geen begrip het vir gestremdes of hulle besondere omstandighede nie. Die meerderheid van hierdie studente ervaar dat hulle nie maklik deur niegestremde studente aanvaar word nie, en hulle vind dit moeilik om met niegestremde studente vriende te maak.
Keywords: Students; Higher education; Impairments; Disabilities; Social needs